SfDronc, an initiator caspase involved in apoptosis in the fall armyworm Spodoptera frugiperda - Huang, Ning (2013)
Initiator caspases are the first caspases that are activated following an apoptotic stimulus, and are responsible for cleaving and activating downstream effector caspases, which directly cause apoptosis. We have cloned a cDNA encoding an ortholog of the initiator caspase Dronc in the lepidopteran insect Spodoptera frugiperda. The SfDronc cDNA encodes a predicted protein of 447 amino acids with a molecular weight of 51 kDa. Overexpression of SfDronc induced apoptosis in Sf9 cells, while partial silencing of SfDronc expression in Sf9 cells reduced apoptosis induced by baculovirus infection or by treatment with UV or actinomycin D. Recombinant SfDronc exhibited several expected biochemical characteristics of an apoptotic initiator caspase: 1) SfDronc efficiently cleaved synthetic initiator caspase substrates, but had very little activity against effector caspase substrates; 2) mutation of a predicted cleavage site at position D340 blocked autoprocessing of recombinant SfDronc and reduced enzyme activity by approximately 10-fold; 3) SfDronc cleaved the effector caspase Sf-caspase-1 at the expected cleavage site, resulting in Sf-caspase-1 activation; and 4) SfDronc was strongly inhibited by the baculovirus caspase inhibitor SpliP49, but not by the related protein AcP35. These results indicate that SfDronc is an initiator caspase involved in caspase-dependent apoptosis in S. frugiperda, and as such is likely to be responsible for the initiator caspase activity in S. frugiperda cells known as Sf-caspase-X.